He-man and the masters of the universe Season two - Lowenthal, Yuri; Rio, Antony Del; Diskin, Ben; Mill Creek Entertainment (United States Mill Creek Entertainment, 2023)
Season two. Includes the episodes: The World Above; The World Below; Eternia 2000; A Very Hungry Dragonfly; Meanwhile...; Divided We Stand; The Battle of Avion; The Fifth Nemesis.
The world above -- The world below -- Eternia 2000 -- A very hungry dragonfly -- Meanwhile... -- Divided we stand -- The battle of Avion -- The fifth nemesis.
Title from container.
Wide screen (1.85:1)
Originally broadcast as single episodes of a television program in 2022.
Yuri Lowenthal, Antony Del Rio, Ben Diskin, Grey Griffin, Kimberly Brooks, David Kaye, Tom Kenny.
Rating: TVY7.
DVD, region 1, NTSC; wide screen (1.85:1); 2.0 Dolby Digital.
Keywords: He-Man -- (Fictitious character) -- Juvenile films; She-Ra -- (Fictitious character) -- Juvenile films; Princes -- Juvenile films; Heroes -- Juvenile films; Good and evil -- Juvenile films; Imaginary places -- Juvenile films; Imaginary wars and battles -- Juvenile films; Animated television programs; Children's films; Fiction television programs; Juvenile works; Television programs; Video recordings for the hearing impaired; Children's television programs